2012
DOI: 10.1371/journal.pone.0039014
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Methylation Profiling of Fetal Tissues Reveals Marked Epigenetic Differences between Chorionic and Amniotic Samples

Abstract: Epigenetic mechanisms including DNA methylation are supposed to play a key role in fetal development. Here we have investigated fetal DNA-methylation levels of 27,578 CpG loci in 47 chorionic villi (CVS) and 16 amniotic cell (AC) samples. Methylation levels differed significantly between karyotypically normal AC and CVS for 2,014 genes. AC showed more extreme DNA-methylation levels of these genes than CVS and the differentially methylated genes are significantly enriched for processes characteristic for the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 39 publications
2
33
1
Order By: Relevance
“…Earlier reports showed that hypermethylated promoters outnumbered hypomethylated promoters in DS chorionic villus samples and leukocytes [18], [27]. In our study, dominance of hypermethylation over hypomethylation in DS was seen in all genomic regions (promoters, intragenic regions, intergenic regions and transcription termination regions, Figure 2A–2F, Table S2), and in all autosomes (Figure 2G).…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Earlier reports showed that hypermethylated promoters outnumbered hypomethylated promoters in DS chorionic villus samples and leukocytes [18], [27]. In our study, dominance of hypermethylation over hypomethylation in DS was seen in all genomic regions (promoters, intragenic regions, intergenic regions and transcription termination regions, Figure 2A–2F, Table S2), and in all autosomes (Figure 2G).…”
Section: Resultssupporting
confidence: 74%
“…We also compared our data with a published report using Illumina HumanMethylation27K BeadChip [18] and identified 2,894 CpGs that were analyzed by both data sets. Good correlation was observed for both normal (r = 0.929) and DS samples (r = 0.913) (Figure S2B–S2C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about epigenetic status in amniocytes. However, a recent study using array-based profiling determined that DNA-methylation levels in amniocytes are extremely high and many genes enriched with low CpG content are hypermethylated [68]. Linking highly expressed transcriptional repressors to specific epigenetic marks in amniocytes will deepen our understanding of their developmental potency.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Nevertheless, placental tissue displays an intermediate distribution of methylation as compared, for example, with embryonal epithelial cells. 16,17 Moreover, there is greater epigenetic variation in extraembryonic than in embryonic tissue. 18 However, it is intriguing to postulate that in some children born small for gestational age (SGA) the underlying cause is a yet unrecognized imprinting disorder.…”
Section: Introductionmentioning
confidence: 99%